In silico and in vitro investigation of curcuminoid as potential TLR4/MD-2 complex inhibitors using molecular docking and molecular dynamic simulations - Tu, Dinh Thi; Chi, Ngo Kim; Huong, Le Thi Thuy; Nghi, Do Huu; Quan, Pham Minh (Vietnam Journal of Science and Technology, 2026)
Inflammation is a key pathological process in many chronic diseases, in which the Toll-like receptor 4/myeloid differentiation factor-2 (TLR4/MD-2) complex serves as a critical upstream regulator. Curcuminoids, naturally occurring polyphenols abundant in Curcuma species cultivated in Vietnam, possess well-documented anti-inflammatory properties; however, their molecular interactions with TLR4/MD-2 remain poorly understood. In this study, an integrated in silico and in vitro strategy was employed to evaluate the anti-inflammatory potential of three major curcuminoids: curcumin, demethoxycurcumin, and bisdemethoxycurcumin. Molecular docking indicated that curcumin and bisdemethoxycurcumin exhibited strong binding affinities toward the TLR4/MD-2 complex, with docking scores of -9.29 and -9.73 kcal/mol, respectively. Molecular dynamics simulations further confirmed the structural stability of these complexes and revealed persistent key interactions. ADMET predictions suggested favorable drug-likeness and low toxicity profiles. Consistently, in vitro assays using LPS-stimulated RAW 264.7 macrophages demonstrated that curcumin and bisdemethoxycurcumin significantly inhibited nitric oxide production, with IC50 values of 121.06 ± 2.16 µM and 91.22 ± 1.58 µM, whereas demethoxycurcumin showed negligible activity. Overall, curcumin and bisdemethoxycurcumin emerge as promising natural compounds for the development of TLR4/MD-2-targeted anti-inflammatory agents.